News Flows, Inter-Media Connectivity and Societal Resilience in Times of Crisis. Issue 7 (9th August 2019) - Steensen, Steen; Eide, Tine
Abstract : This article analyzes how inter-media connections and news flows can establish societal resilience in times of crisis. The article is framed by understandings of the discursive practice of news as polyvocal and networked, and that social media as much as legacy media are important to a society's resilience to crisis situations. Based on an analysis of the Norwegian public sphere during and immediately after the terrorist attacks of 22 July 2011, the article finds that the Norwegian public sphere established societal resilience through what we identify as "uniformed polyvocality". This analysis reveals that an inter-connected news landscape, in which power is distributed and trust in established news institutions is intact, is key to the formation of societal resilience in times of crisis. The analysis is based on the following empirical material: Hyperlinks in the Norwegian Twitter-sphere and in online news sites, and sources referenced in stories about the attacks published in the most read Norwegian online and print news outlets. The findings, and the methodology presented in this article, have important implications for future research related to discursive practices of news and societal resilience in times of crisis.